Understanding why we age and how: Evolutionary biology meets different model organisms and multi‐level omics: Meeting report on "Comparative Biology of Aging, " Roscoff, October 12–16, 2015. (27th April 2016) - Gilson, Eric; Bosch, Thomas C. G.
Abstract : The conference explored an extraordinary diversity of aging strategies in organisms ranging from short‐lived species to "immortal" animals and plants. Research on the biological processes of aging is at the brink of a revolution with respect to our understanding of its underlying mechanisms as well as our ability to prevent and cure a wide variety of age‐related pathologies.